EVALUATION OF DISTANCE HIGHER EDUCATION PRACTICES IN TURKEY: THE DEVELOPMENT OF ASSOCIATE DEGREE AND UNDERGRADUATE PROGRAMS - Çekerol, Kamil (PEOPLE: International Journal of Social Sciences, 2018)
Since the beginning of the year 2000, the number of higher education institutions offering open and distance education in Turkey has been increasing, and many universities have been offering associate degree and undergraduate education by open and distance education method. Recent legislative arrangements divided distance education into two modes. While many higher education institutions that meet the required criteria are categorized as "distance education", three universities among them offer “open education” with more emphasis on mass teaching. This study assesses the development of distance learning on the basis of programs offered in the last ten years by focusing on the place of distance education programs among all the other university programs, the applications of higher education institutions to associate degree and undergraduate degree programs, the quota restrictions on the programs and on the number of enrollments, and the program diversity and progress. For this purpose, all distance education programs implemented by the universities since 1996 are explored and analysed as they are presented in the guidebooks Council of Higher Education published on web sites, and in the web pages of the related universities. The results show that higher education institutions involved in distance education cannot continue their programs because of quota restrictions and the number of students enrolled. It is important to review the issues related to organizational, managerial, financial and other legislation, as well as the quota and enrolment problems for the development of distance education programs.